Formation of Ecological Culture of Primary School Students - Jobborova Gulnoza Kadamovna (Genius Publishing Group, 2022)
In the article are considered forms and methods of inter subject ecological education on the lessons of natural history in initial classes. The author offers scenario of lessons in initial classes, that have to assists adjusting of work on ecological education, developed by him.
Keywords: Inter Subject Education; Ecology; Form; Method